2022
DOI: 10.3390/w14132069
|View full text |Cite
|
Sign up to set email alerts
|

Improving Environmental DNA Sensitivity for Dreissenid Mussels by Targeting Tandem Repeat Regions of the Mitochondrial Genome

Abstract: The recent genetic revolution through the analysis of aquatic environmental DNA (eDNA) has become a powerful tool for improving the detection of rare and/or invasive species. For the majority of eDNA studies, genetic assays are designed to target mitochondrial genes commonly referred to as “barcode” regions. However, unlike the typical structure of an animal mitochondrial genome, those for the invasive zebra and quagga mussels are greatly expanded with large extended tandem repeat regions. These sections of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Moreover, the LOD obtained for the pDRB1 assay in this study was 100 copies/µL. While Blackman et al (2020b) had previously reported a LOD of 1E-04 ng/μL for the dDRB1 assay with SYBR green dye, and Marshall, Vanderploeg & Chaganti (2022) found the LOD to be 9.8E-05 ng/reaction for the same assay with the EvaGreen dye, the different units used to assess limits of detection (ng/μL and copies/μL) makes the direct comparison between LODs not fair.…”
Section: Pdrb1 Assaymentioning
confidence: 47%
“…Moreover, the LOD obtained for the pDRB1 assay in this study was 100 copies/µL. While Blackman et al (2020b) had previously reported a LOD of 1E-04 ng/μL for the dDRB1 assay with SYBR green dye, and Marshall, Vanderploeg & Chaganti (2022) found the LOD to be 9.8E-05 ng/reaction for the same assay with the EvaGreen dye, the different units used to assess limits of detection (ng/μL and copies/μL) makes the direct comparison between LODs not fair.…”
Section: Pdrb1 Assaymentioning
confidence: 47%